Very highly efficient reduction of CO2 to CH4 using metal-free N-doped carbon electrodes. Issue 4 (27th January 2016) - Sun, Xiaofu; Kang, Xinchen; Zhu, Qinggong; Ma, Jun; Yang, Guanying; Liu, Zhimin; Han, Buxing
Abstract : We report the first work on the electrocatalytic reduction of CO2 to CH4 using metal-free N-doped carbon electrodes. Abstract : The electrocatalytic reduction of CO2 to energy-rich chemicals is a promising pathway for energy storage and utilization. Herein we report the first work on the electrocatalytic reduction of CO2 to CH4 using metal-free electrodes. It was found that N-doped carbon (graphene-like) material/carbon paper electrodes were very efficient for the electrochemical reaction when using ionic liquids (ILs) as the electrolytes. The faradaic efficiency of CH4 could be as high as 93.5%, which is the highest to date. The current density was about 6 times higher than that of a Cu electrode under similar conditions, which is the well-known effective electrode for the electrocatalytic reduction of CO2 to CH4 . Additionally, a trace amount of water in the IL could improve the current density effectively without reducing CH4 selectivity considerably. Our results highlight a new class of low-cost and designable electrocatalysts for synthetic fuel production from CO2 .